Global health competencies in postgraduate medical education: a scoping review and mapping to the CanMEDS physician competency framework - Pritchard, Jodie; Alavian, Sara; Soogoor, Anantha; Bartels, Susan; Hall, Andrew (Canadian Medical Education Journal, 2023)
Background: Global Health opportunities are popular, with many reported benefits. There is a need however, to identify and situate Global Health competencies within postgraduate medical education. We sought to identify and map Global Health competencies to the current CanMEDS physician competency framework to assess the degree of equivalency and uniqueness between them. Methods: JBI scoping review methodology was utilized to identify relevant papers searching MEDLINE, Embase, and Web of Science. Studies were reviewed independently by two of three researchers according to pre-determined eligibility criteria. Included studies identified competencies in Global Health training at the postgraduate medicine level, which were then mapped to the CanMEDS framework. Results: A total of 19 articles met criteria for inclusion (17 from literature search and 2 from manual reference review). We identified 36 Global Health competencies; the majority (23) aligned with CanMEDS competencies within the framework. Ten were mapped to CanMEDS roles but lacked specific key or enabling competencies, while three did not fit within the specific CanMEDS roles. Conclusions: We mapped the identified Global Health competencies, finding broad coverage of required CanMEDS competencies. We identified additional competencies for CanMEDS committee consideration and discuss the benefits of their inclusion in future physician competency frameworks.